2021
DOI: 10.1155/2021/5595478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Polycystic Ovary Syndrome in Animal Models: A Systematic Review

Abstract: Background. Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders among women of reproductive age. As a widely used complementary and alternative therapy, acupuncture is increasingly used to treat PCOS. However, the effect of acupuncture in treating PCOS is uncertain, and the mechanisms are unclear. This systematic review aims to determine the efficacy of acupuncture on PCOS in animal preclinical models. Methods. Experimental animal studies of acupuncture in PCOS animal models were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition, our multinational study protocol on acupuncture or metformin to improve insulin resistance in women with PCOS has been published ( 124 ). In recent years, there have been an increasing number of systematic reviews and/or meta-analyses on the effect of acupuncture on PCOS in both patients and animal models ( 22 , 23 , 96 , 100 ). This study reviewed the feasibility and efficacy of acupuncture for managing PCOS and summarized the potential mechanisms of acupuncture on treating PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, our multinational study protocol on acupuncture or metformin to improve insulin resistance in women with PCOS has been published ( 124 ). In recent years, there have been an increasing number of systematic reviews and/or meta-analyses on the effect of acupuncture on PCOS in both patients and animal models ( 22 , 23 , 96 , 100 ). This study reviewed the feasibility and efficacy of acupuncture for managing PCOS and summarized the potential mechanisms of acupuncture on treating PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that acupuncture elevates the level of β-endorphin not only in the central endocrine system but also in the peripheral circulation ( 94 ), which is associated with both direct and indirect tonic inhibitions of GnRH and subsequent LH release ( 132 ). Aberrant sympathetic neurogenic regulation of the ovary is involved in the pathogenesis of PCOS ( 23 ), and acupuncture can also inhibit the overexpression of NGF to decrease sympathetic activity, resulting in a restoration to the normal level of the ovarian steroid response to gonadotropins ( 25 ). Moreover, acupuncture regulates the phosphorylation of insulin substrates and receptors and inhibits the abnormal expression of signaling pathways, thereby improving metabolic dysfunction such as insulin resistance ( 32 , 56 , 133 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroacupuncture (EA) has a benign regulating effect on neuroendocrine levels in organs. A more recent meta-analysis indicated that acupuncture might have the potential to restore hormone levels in PCOS animal models [ 22 ]. Repeated low-frequency EA inhibited the expression of GnRH and NPY in the hypothalamus of early adolescent Sprague Dawley (SD) female rats [ 23 ].…”
Section: Introductionmentioning
confidence: 99%